Mediastinal Mass and Pleural Effusion: different clinical presentations of lymphoma in pediatric age - Federica Maria Previtera; Simone Foti Randazzese; Fabio Toscano; Santo Ielo; Maria Emanuela Chessari; Mariapia Composto; Flavia Caime; Sara Manti; Carmelo Romeo; Malgorzata Gabriela Wasniewska; Giuseppina Zirilli (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2025)
Background: Mediastinal masses and pleural effusions may have different etiologies, from infectious to malignant and autoimmune diseases, originating from the mediastinum or nearby structures. Several signs and symptoms, such as persistent anemia, dyspnea, chronic itching, and mantle oedema, may raise suspicion of a malignant disease. Specifically, lymphomas may be a common cause of both mediastinal masses and pleural effusions.